2006 Florida Plant Disease Management Guide: Guava (Psidium guajava) - Michael Merida; Aaron J. Palmateer (EDIS, 2006)
PP-232, a 9-page fact sheet by Michael Merida and Aaron J. Palmateer, describes several diseases of guava caused by fungi and stramenopile, describing the symptoms, causal organism, disease cycle and epidemiology, and management for each. Includes references. Published by the UF Plant Pathology Department as part of the Plant Disease Management Guide, June 2006.